Impact of elevated temperature on rubberized concrete: A review - Alaloul, W.S. (Springer Science and Business Media Deutschland GmbH, 2021)
Excessive production of non-biodegradable scrap tyres will bring a negative impact to the environment, thus recycling crumb rubber as partial replacement of construction material such as concrete can effectively reduce the bulking of solid waste in the dumping area. However, the partial replacement of fine aggregate in concrete with crumb rubber reflected a decrease in mechanical properties of rubberized concrete compared to the ordinary concrete mix. Concrete is sensitive to the elevated temperature and when it comes to the rubberized concrete, the changes are more significant as compared to normal concrete. With high temperature rubber starts melting which impact in the reduction of mechanical properties of rubberized concrete, thus failure in the specimen occurs. Therefore, in this study, the impact of elevated temperature on the compressive strength and the tensile strength of rubberized concrete has been reviewed. Â© The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2021.